2017
DOI: 10.1515/jbcpp-2016-0100
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of salusin-α and salusin-β against ethanol-induced gastric ulcer in rats

Abstract: Background: Alcohol consumption has been found to be associated with gastric ulcers, including gastric mucosal lesions. Salusin-α and salusin-β are bioactive peptides having 28 and 20 amino acids, respectively. Salusin-α and salusin-β immunoreactivity has been detected in the stomach and in the intestines. It has been reported that the salusins regulate the cytokine levels and decrease the infarct area in the heart tissue after ischemia. In this study, we investigated the effects of the salusins in the gastric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…Previous studies reported that pretreatment with excess salusin-α did not attenuate the salusin-β-induced increase in intracellular calcium in VSMCs [10], suggesting that they do not compete for the same receptors. Because salusin-α and -β have quite distinct sequences, we speculate that they may bind to different receptors, although this hypothesis has not been fully verified [33]. A recent study reported that salusin-β, but not salusin-α, promotes vascular inflammation in ApoE-deficient mice [34].…”
Section: Discussionmentioning
confidence: 91%
“…Previous studies reported that pretreatment with excess salusin-α did not attenuate the salusin-β-induced increase in intracellular calcium in VSMCs [10], suggesting that they do not compete for the same receptors. Because salusin-α and -β have quite distinct sequences, we speculate that they may bind to different receptors, although this hypothesis has not been fully verified [33]. A recent study reported that salusin-β, but not salusin-α, promotes vascular inflammation in ApoE-deficient mice [34].…”
Section: Discussionmentioning
confidence: 91%
“…Salusin- α is derived from the torsin family 2 member A ( TOR2A ) gene, which is transcribed into preprosalusins and subjected to alternative splicing. Salusin- α is a multifunctional bioactive peptide with 28 amino acid residues that functions to prevent the restenosis of arteries [ 10 , 11 ]. In addition, this protein is also involved in the prevention of macrophage foam cell formation by downregulating acetyl-coenzyme A acetyltransferase 1 (ACAT1), thereby affecting atherosclerosis [ 10 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Apoptosis cascade is a significant pathway mediating ethanol-induced gastric ulcer, which is also associated with inflammatory response and oxidative stress 45 . In this regard, ethanol-induced gastric ulcer enhances caspase-3 expression 16 .…”
Section: Discussionmentioning
confidence: 99%
“…It can also lead to vascular permeability and even cell lysis 27 . Ethanol-induced gastric ulcer in experimental animals is one of the most common ulcer models examining various compounds for determining antiulcer effects 16 . The current study revealed that PYR has preventive activity against ethanol-induced gastric ulcer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation